2008
DOI: 10.1002/elan.200804347
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Glassy Carbon Electrode With Single‐Walled Carbon Nanotubes and α‐Silicomolybdate: Application to Sb(III) Detection

Abstract: A simple procedure was developed to prepare a glassy carbon (GC) electrode modified with single-walled carbon nanotubes (SWCNTs) 4À and CNTs. In this research the attractive mechanical and electrical characteristics of CNTs and unique properties and reactivity of polyoxometalates were combined. The modified electrode in buffer solution containing Sb(III) shows a new redox system at 0.38 V in pH 1. The voltammetric peak current increased with increasing Sb(III) concentration. The differential pulse voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 76 publications
0
11
1
Order By: Relevance
“…These are summarized in Table 3. As can be seen from this table, the value of LOD is lower than most of the reported electrochemical methods [15,16,[21][22][23]26,[31][32][33]36,[38][39][40]43,45,49,52]. Moreover, the results of the interference studies showed that the selectivity of the proposed method is quite high.…”
Section: Comparison Of Proposed Methods With Other Methodscontrasting
confidence: 42%
See 4 more Smart Citations
“…These are summarized in Table 3. As can be seen from this table, the value of LOD is lower than most of the reported electrochemical methods [15,16,[21][22][23]26,[31][32][33]36,[38][39][40]43,45,49,52]. Moreover, the results of the interference studies showed that the selectivity of the proposed method is quite high.…”
Section: Comparison Of Proposed Methods With Other Methodscontrasting
confidence: 42%
“…Furthermore, the measurement period is very short. In addition, when the proposed method including the use of GCE in the presence of RIV was compared with studies performed using GCE together with other modifiers for determination of Sb(III), it exhibited better LOD and a larger linearity range than those studies [21,26].…”
Section: Comparison Of Proposed Methods With Other Methodsmentioning
confidence: 99%
See 3 more Smart Citations